Convenient synthesis of 5-methylene-4-substituted-2(5H)-furanones - Mahajan, Vishal A.; Shinde, Popat D.; Borate, Hanumant B.; Wakharkar, Radhika D. (Tetrahedron Letters, 2005)
A synthesis of novel 4-(substituted)benzyl-5-methylene-2(5H)-furanones involving Stobbe condensation of substituted aldehydes with ethyl levulinate followed by treatment with acetic anhydride in the presence of sodium acetate, has been developed. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: 5-methylene-2(5H)-furanones; acetic anhydride; arylaldehydes; ethyl levulinate; sodium acetate